Bianca - Small, Bertrice (Small, Bertrice. Silk merchant's daughters., 2013)
Florentine silk merchant Giovanni Pietro d'Angelo and his wife want only to marry their daughters to wealthy men of distinction. But when their son's indiscretion implicates him in a tragic accident, their eldest daughter must pay the price. To buy the silence of Sebastiano Rovere, they must give beautiful Bianca to him in marriage. But Bianca flees this cruel union, and then her husband's shocking murder frees Bianca to love at last.